(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the occurrence, contributing factors and risks associated with home drug storage, as well as to configure the importance of pharmaceutical care in this field. Method: Literature review through the identification of articles published in the Scielo, Pubmed and Medline databases during the period. 2007 and 2020, using as descriptors: ’pharmaceutical care’, ’medicines’, ’home’, ’rational use’, ’self-medication’, ’storage’, with insertion in observational studies and original articles. Results: It is common to store medicines at home, imposing the need to store them safely. According to the findings, the drugs commonly stocked are those over-the-counter, used to treat fever, diarrhea, vomiting and colds, easily acquired, and leftover treatments. It was also observed in the review performed the high frequency of improper storage (exposure to light, heat and humidity) and unreadable expiration date and batch number, where these conditions favor the risk of overdose poisoning, misuse and interactions drug Conclusion: It was notorious that the storage of medicines at home is a common practice among the world population. This practice is then associated with the irrational use of medicines and drug poisoning, putting people’s health at risk. It is emphasized the determining importance of the professional pharmacist’s role in primary and family pharmaceutical care, as well as in community pharmacies to outline strategies that corroborate the solution of this problem.